2016
DOI: 10.1016/j.rvsc.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A WUR SNP is associated with European Porcine Reproductive and Respiratory Virus Syndrome resistance and growth performance in pigs

Abstract: Porcine reproductive and respiratory syndrome (PRRS) causes decreased reproductive performance and respiratory problems in pigs. The goals of the current study were 1) to examine whether individual variation applies to infection with PRRSV European strains and 2) to investigate the association of a single nucleotide polymorphism (SNP) WUR10000125 (WUR) at the interferon-inducible guanylate-binding protein 1 gene (GBP1) with average daily gain (ADG) in PRRSV infected and uninfected pigs. The experimental proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
3
29
0
2
Order By: Relevance
“…Genetic analyses of the first two trials by Dunkelberger et al (2017) demonstrated a low to moderate genetic basis for host response to PRRS vaccination (PRRS VL and WG) and to co-infection (PRRS and PCV2b VL and WG with or without prior vaccination), with heritabilities ranging from 0.07 to 0.57. Genotype at the WUR SNP had a significant association with host response, both post vaccination and post coinfection: post-vaccination, AB pigs had lower vaccine virus VL and faster gain than AA pigs, confirming results by Abella et al (2016) for vaccination with an attenuated European strain of the PRRSV. Post coinfection, AB pigs had lower PRRSV VL but did not significantly differ from AA pigs in growth rate.…”
Section: Co-infection Trialssupporting
confidence: 56%
See 3 more Smart Citations
“…Genetic analyses of the first two trials by Dunkelberger et al (2017) demonstrated a low to moderate genetic basis for host response to PRRS vaccination (PRRS VL and WG) and to co-infection (PRRS and PCV2b VL and WG with or without prior vaccination), with heritabilities ranging from 0.07 to 0.57. Genotype at the WUR SNP had a significant association with host response, both post vaccination and post coinfection: post-vaccination, AB pigs had lower vaccine virus VL and faster gain than AA pigs, confirming results by Abella et al (2016) for vaccination with an attenuated European strain of the PRRSV. Post coinfection, AB pigs had lower PRRSV VL but did not significantly differ from AA pigs in growth rate.…”
Section: Co-infection Trialssupporting
confidence: 56%
“…The smaller effects of this major gene for the KS06 strain, in particular for WG, may reflect the lower pathogenicity of the KS06 strain, consistent with the lower VL and higher WG observed for that strain compared to the NVSL strain. Abella et al (2016) recently showed that genotype at WUR was also associated with growth rate following vaccination with an attenuated European strain of the PRRSV. However, when pigs were challenged with a wild-type European PRRSV strain, genotype at WUR was not significantly associated with VL, although pigs with the AB genotype had numerically lower VL (Abella et al, 2016).…”
Section: Discovery Of a Major Gene For Host Response To Prrsvmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is difficult to estimate the impact of slight genetic differences on the immunogenicity of the vaccine virus and the protection upon challenge (PRRSV strains DV and Lena have an identity of 88 % whereas VP-046 BIS and Lena have an 82.5 % identity (ORF5)). The different outcomes between both studies cannot be related to the genetic background in our opinion, as the piglets came from the same farm [30,31]. The major difference between both studies was the vaccination-challenge interval.…”
Section: Discussionmentioning
confidence: 88%